Kajian Kondisi Drainase Jalan Perkotaan (Studi Kasus: Kecamatan Pekalongan Utara, Kota Pekalongan) - sutrisno, prasetyo aji; Sakinah; Herol; Juse Roejanto (JURNAL TEKNIK SIPIL, 2025)
In Pekalongan City, particularly on Perintis Kemerdekaan Street and Patriot Street, waterlogging frequently occurs during the rainy season due to ineffective drainage systems. The main causes are narrowed drainage channels, sediment buildup, waste accumulation, and wastewater discharge from nearby residential areas. These streets are vital access points to offices, schools, and trade centers, making the waterlogging a significant disruption to economic activities and the community. According to the analysis, the peak discharge on Perintis Kemerdekaan Street for a 5-year period is 24.305 m³/s, while the channel's capacity is only 18.869 m³/s. On Patriot Street, the peak discharge is 3.575 m³/s, with a channel capacity of 46.427 m³/s. Although the drainage capacity in both locations is adequate to accommodate the peak discharge, waterlogging still occurs due to external factors such as sediment and waste clogging the drains, along with heavy rainfall.